A FEM model for lifetime prediction of Ancorsteel1000C in rolling contact fatigue. Issue 1 (December 2014) - Özden, U.A.; Giang, N.A.; Chen, G.; Bezold, A.; Broeckmann, C.
Abstract Ancorsteel1000C is commonly used for important components including bearing rollers, gears, connecting rods, wheels and rails; most failures of these components are caused by rolling contact fatigue (RCF). In this study the fatigue damage indicator based on Fatemi‐Socie critical plane were determined in a local hot spot area in finite element (FE) model in case of Hertzian stress with zero slip condition. The simulation results compared with respect to experimental data, which is in good agreement. Therefore, this approach can be implemented as a useful tool for lifetime calculations in RCF in the process of structure fatigue design. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)